HARMONY OF POLITICAL, ECONOMIC CULTURE IS A FACTOR OF DEVELOPMENT - Gulnoza Nasrullayeva (Scholar Express Journal, 2023)
Political culture, as an element of a single integrated system, is closely related to other parts of general culture. That is, political culture is considered the system-forming core of the general culture and affects all types of culture. Because, in order to raise the culture of the society, first of all, a high political culture is necessary. Political culture as a normative system is interconnected with legal culture. These two types of culture are criteria that determine the norms of behavior of a person in society and his attitude to society. Such processes are related to economic culture
Keywords: Political culture; society culture; economic culture